A framework for data security, privacy, and trust in "consumer internet of things" assemblages in South Africa. Issue 5 (8th July 2020) - Ngwenya, Mfanasibili; Ngoepe, Mpho
Abstract: The Internet of Things (IoT) brings opportunities and challenges to humankind. IoT technology makes it possible to connect all of a person's devices to create a smart ecosystem. However, IoT has also raised issues of data security, privacy, and trust to the consumer. In a world where cybercriminals have enormously increased, people need to be aware of the advantages, and the risks that come with these technological advances. This study conducted a literature review to develop a framework to address the issues of data security, privacy, and trust in consumer IoT (CIoT). The study suggested an integrated and holistic framework that promotes safer adoption of CIoT. The researchers concluded that for CIoT to thrive, safety is crucial, and all the stakeholders in the IoT assemblage need to ensure the protection of consumers. The suggested framework may assist in the protection of consumers of IoT, data trust, as well as trust in the CIoT assemblage. It covers the concerns, experiences, and adaptations of consumers of IoT regarding data security, privacy, and trust concerning technology and privacy legislation in South Africa.